Screening of Flavivirus in mosquitoes in Peninsular Malaysia - Abd Rahaman, Nor Yasmin; Ishak, Nur Syafiqah; Jafar Ali, Natasha; Arshad, Siti Suri; Mustaffa, Kamal Farina; Saulol Hamid, Nur Fazila (Malaysian Association of Veterinary Pathology, 2024)
Flavivirus such as West Nile virus (WNV) and Japanese Encephalitis virus (JEV) are primarily transmitted by mosquitoes, and the infection causes a significant public health concern particularly in Malaysia. Both virus infection is mainly maintained and amplified in reservoir hosts which are wild birds. Mosquitoes from migratory bird areas were collected using CDC light traps and were screened for WNV and JEV using RT-PCR. These localities were selected based on their association with JEV reservoirs and dynamics of transmission. Results indicated WNV was detected but no evidence of JEV in any of the collected mosquitoes. This study highlights the need for continued surveillance and further investigation into the epidemiological and ecological factors influencing Flavivirus transmission dynamics in Malaysia.